Metal–Organic-Framework-Based Materials for Antimicrobial Applications - Li, Rui; Chen, Tongtong; Pan, Xiangliang (ACS nano, 2021)
To address the serious threat of bacterial infection to public health, great efforts have been devoted to the development of antimicrobial agents for inhibiting bacterial growth, preventing biofilm formation, and sterilization. Very recently, metal–organic frameworks (MOFs) have emerged as promising materials for various antimicrobial applications owing to their different functions including the controlled/stimulated decomposition of components with bactericidal activity, strong interactions with bacterial membranes, and formation of photogenerated reactive oxygen species (ROS) as well as high loading and sustained releasing capacities for other antimicrobial materials. This review focuses on recent advances in the design, synthesis, and antimicrobial applications of MOF-based materials, which are classified by their roles as component-releasing (metal ions, ligands, or both), photocatalytic, and chelation antimicrobial agents as well as carriers or/and synergistic antimicrobial agents of other functional materials (antibiotics, enzymes, metals/metal oxides, carbon materials, etc.). The constituents, fundamental antimicrobial mechanisms, and evaluation of antimicrobial activities of these materials are highlighted to present the design principles of efficient MOF-based antimicrobial materials. The prospects and challenges in this research field are proposed.